Answer:A
Step-by-step explanation:
Answer:
B) -1-6 x +15 = x - 15 +15
Step-by-step explanation:
<u>Explanation</u>:-
Given equation is –1 – 6 x = x – 15
<em>By addition property of equality </em>
<em> ⇒ - 1 - 6 x + 15 = x - 15 +15</em>
⇒ - 6 x + 14 = x
subtracting 'x' on both sides ,we get
⇒ - 6 x -x +14 =0
⇒ - 7 x +14 =0
⇒ -7 x = - 14
Dividing '-7' on both sides , we get
x = 2
<em>The solution of given equation is x = 2</em>
Answer:
⅖
Step-by-step explanation:
5x = 2
x = ⅖
⅖ can't be simplified further